Estudio de factibilidad para la creación de una empresa dedicada al servicio de troquelado para la industria gráfica, en el Distrito Metropolitano de Quito - Artos Andino, Marcia Susana (2015)
The development of this research held in a methodology proposed by the University, which I structure into five chapters. Is a synthesis of the history of the printing industry worldwide, as then in the country; the graphic production process is identified and is known on die-cutting, types of equipment, etc. In addition the thesis plan scheme develops in its most important aspects that are the approach to the problem, rationale and objectives. Study sample size, target market, tabulation and analysis of the results, whose findings resulted in a report. Identified the optimal location, installed capacity of machines, etc. On the administrative side organized the enterprise through flow charts; and the number of staff required as its main functions was determined. In the legal aspect, it gives to know the process or steps to follow for the legal Constitution of the company. Study economic and financial determined the investment of the project, form of financing, credit, was identified and calculated the costs and revenues on the basis they prepared budgeted balances; was the cash flow for the project, who served at the same time to calculate the VAN, recovery period of investment (PRI).